Response Time, Decision Time, and Delivery Time in Pediatric Emergency Unit of West Java Top Referral Hospital - Oktaviani, Ayu Sary; Lukmanul Hakim, Dzulfikar D.; Suwarman, Suwarman (Althea Medical Journal, 2017)
Background: The number of visitors at pediatric emergency unit has increased around 25 million per year. This condition caused overcrowded in these units which would disrupt health care process. Waiting time is one indicator of health care quality. Prolonged waiting times is related to patientâs dissatisfaction and poor outcome. The aim of this study was to identify response time, decision time, and delivery time of Pediatric Emergency Unit in Dr. Hasan Sadikin General Hospital.Methods: This was a descriptive cross sectional study. Data from medical records of pediatric patients who attend Pediatric Emergency Unit, Dr. Hasan Sadikin General Hospital from August to September 2015 were collected. The data included sex, age, day of admission, time of admission, insurance status, triage status, disposition of care, response time, decision time, and delivery time. The collected data were analyzed and presented in percentage and peformed in tables. Results: A total of 201 data were collected during study period. The geometric mean of total waiting time in pediatric emergency department was 346.65 minutes (5 hours 46 minutes). Response time had a geometric mean of 4.07 minutes, meanwhile decision time and delivery time had geometric mean of 46.77 minutes and 181.97 minutes, respectively.Conclusions: Total waiting times of pediatric emergency department exceeds the standard time (4 hours). Meanwhile response time and decision time have already met the standard.Â